АСТРОНОМИК КООРДИНАТАЛАР ТИЗИМЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article discusses the astronomical coordinate systems, the name of the stars, and their position in the celestial sphere and solve various astronomical problems to determine the coordinates of the various star systems.